2012
DOI: 10.1016/b978-0-12-398315-2.00002-8
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Warming on the Structure and Functioning of Aquatic Communities

Abstract: Environmental warming is predicted to rise dramatically over the next century, yet few studies have investigated its effects in natural, multi-species systems. We present data collated over an 8-year period from a catchment of geothermally heated streams in Iceland, which acts as a natural experiment on the effects of warming across different organisational levels and spatiotemporal scales. Body sizes and population biomasses of individual species responded strongly to temperature, with some providing evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
210
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 131 publications
(222 citation statements)
references
References 268 publications
(296 reference statements)
6
210
1
Order By: Relevance
“…Biofilm-grazing gastropods represent common consumers or competitors of ciliates, and temperature is known to increase both the feeding rate and the activity rate of gastropods (Yee & Murray 2004). In our study system, Radix balthica snails play a key role in the food web, being the dominant large grazer in Hengill streams (O'Gorman et al 2012). Radix balthica consumes the same resources (bacteria and diatoms) as many protists, and it is more abundant and exerts higher grazing pressure on the biofilm at high temperatures (O'Gorman et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Biofilm-grazing gastropods represent common consumers or competitors of ciliates, and temperature is known to increase both the feeding rate and the activity rate of gastropods (Yee & Murray 2004). In our study system, Radix balthica snails play a key role in the food web, being the dominant large grazer in Hengill streams (O'Gorman et al 2012). Radix balthica consumes the same resources (bacteria and diatoms) as many protists, and it is more abundant and exerts higher grazing pressure on the biofilm at high temperatures (O'Gorman et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In our study system, Radix balthica snails play a key role in the food web, being the dominant large grazer in Hengill streams (O'Gorman et al 2012). Radix balthica consumes the same resources (bacteria and diatoms) as many protists, and it is more abundant and exerts higher grazing pressure on the biofilm at high temperatures (O'Gorman et al 2012). The increased abundance and grazing pressure of R. balthica at high temperatures may reduce the species richness and total biomass in ciliate assemblages, either by direct competition for resources, by physically displacing ciliates while grazing the biofilm, or by consuming them directly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, McAbendroth et al (2005) found that increasing macrophyte habitat complexity was v www.esajournals.org associated with a greater number of small-bodied individuals. Size structure in turn affects a system's capacity to support predator biomass due to reduced trophic transfer efficiencies associated with smaller prey (O'Gorman et al 2012). Consequently, despite increasing ecosystem productivity, eutrophication can actually reduce the amount of available energy for stream food webs, because the increased productivity is largely trapped in defended primary production (macrophytes), which in turn favors defended primary consumers, thus creating energy bottlenecks at multiple trophic levels (Fig.…”
Section: Community Composition and Trophic Interactionsmentioning
confidence: 99%